A winter wonderland - Michaels, Fern; Michaels, Fern; Chamberlin, Holly, 1962-; Meier, Leslie; McMorris, Kristina (Zebra books, 2012)
A collection of four Christmas love stories includes Fern Michaels' "A Winter Wonderland," in which Angelica Shepard wakes up in the hospital after an accident with only the memory of the handsome angel who saved her.